Between marginalisation and integration: practising deaf sports in interwar Romania. Issue 5 (4th May 2022) - Rotar, Marius
Abstract: The emergence and the development of deaf sports represent a neglected topic by historians. The importance of this topic consists on highlighting of the efforts for the integration of the deaf people into sports movement and society as a whole into certain period of time. The aim of this article is to take into the light the ways in which deaf sports appeared in interwar Romania and the different difficulties which this initiative encountered. In this manner, there are emphasized the creation of the 'Deaf-and-Dumb Cultural and Sports Club' in Bucharest (1934), the fruitless endeavors of Vasile Dimitriu-Leorda for admission of deaf football teams in the competitions organized by the Romanian Football Federation, the creation of Romania's deaf national team (1938), and, also, Romania's participation in the 1939 Stockholm Summer Deaflympics.